Seasonal Level Change and Overdraft of Water Wells - Şekerci, Kürşat; Tuna, Cihat; Doğan, Mustafa Şahin (My University, 2023)
In the simplest terms an overdraft, can be expressed as a condition in which the water withdrawn from an underground water aquifer by pumping exceeds the amount that recharges the aquifer via deep percolation. Groundwater aquifers are fed by infiltration from precipitation, surface water bodies, such as rivers and lakes when they are hydraulically connected, and return flows from agricultural and urban uses. Groundwater overdraft is an unsustainable use of limited water resources. Less surface water availability due to rising temperatures and lack of precipitation, and pollution of aquifers are among reasons for excessive groundwater overdraft. In addition to such negative factors, uncontrolled agricultural irrigation also increases the effect of overdraft. For such reasons, it is important to protect the waters with the understanding of sustainable management. In this study, seasonal water heights in observation wells operated at the same water elevation in two different resorts located on the borders of the Uluova basin were examined and water level changes were examined. The periodic (seasonal) water heights of the observation wells in 2011 and 2018 were studied. The effect of overdraft was pointed out through the height changes in the observation wells.
Keywords: Basin; Overdraft; Observation Well